2021
DOI: 10.1186/s12967-021-02956-6
|View full text |Cite
|
Sign up to set email alerts
|

MYBL2-induced PITPNA-AS1 upregulates SIK2 to exert oncogenic function in triple-negative breast cancer through miR-520d-5p and DDX54

Abstract: Background In recent years, long non-coding RNAs (lncRNAs) have attracted much attention because of its regulatory role in occurrence and progression of tumors, including triple-negative breast cancer (TNBC). LncRNA PITPNA antisense RNA 1 (PITPNA-AS1) has been explored in some cancers, whereas its function and molecular mechanism in TNBC remain unclear. Methods PITPNA-AS1 expression in TNBC tissues and cells was determined by RT-qPCR. TNBC cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…lncRNAs have received a lot of attention in recent years, and they have played a pivotal role in various malignancies, notably LUSC. [10][11][12][13][14] PITPNA-AS1 is a novel lncRNA that has been investigated in LUSC to accelerate tumorigenesis. 16 However, the ceRNA regulation mechanism mediated by PITPNA-AS1 in LUSC is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lncRNAs have received a lot of attention in recent years, and they have played a pivotal role in various malignancies, notably LUSC. [10][11][12][13][14] PITPNA-AS1 is a novel lncRNA that has been investigated in LUSC to accelerate tumorigenesis. 16 However, the ceRNA regulation mechanism mediated by PITPNA-AS1 in LUSC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PITPNA antisense RNA 1 (PITPNA‐AS1) has been identified as a new lncRNA that has a role in the progression of a variety of malignancies. In triple‐negative breast cancer, PITPNA‐AS1 has been shown to have an oncogenic role by targeting the miR‐520d‐5p/DDX54 axis 14 . PITPNA‐AS1 also absorbs miR‐129‐5p to control UNC5B and accelerates papillary thyroid tumorigenesis 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our studies showed that LINC01608 was overexpressed in HCC and functioned as a ceRNA for miR‐875‐5p to promote HCC progression. Additionally, recent studies had demonstrated that some transcriptional factors, such as SP1 and MYBL2, could combine with the promoter of LncRNAs and regulate their expression 24,25 . YY1 is a transcriptional factor ubiquitously expressed in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has found that MYBL2 overexpression plays an oncogenic role in cancers, such as colorectal cancer and hepatocellular carcinoma [ 12 , 13 ]. MYBL2-induced PITPNA antisense RNA 1 (PITPNA-AS1) upregulates salt-inducible kinase 2 (SIK2) to exert oncogenic functions in triple-negative breast cancer [ 14 ]. Besides, MYBL2 was reported to play important regulatory roles in proliferation, differentiation, and cell cycle [ 15 ].…”
Section: Introductionmentioning
confidence: 99%